Plasmonic hotspots in air : an omnidirectional three-dimensional platform for stand-off in-air sers sensing of airborne species - Phan-Quang, Gia Chuong (2019)
Molecular‐level airborne sensing is critical for early prevention of disasters, diseases, and terrorism. Currently, most 2D surface‐enhanced Raman spectroscopy (SERS) substrates used for air sensing have only one functional surface and exhibit poor SERS‐active depth. “Aerosolized plasmonic colloidosomes” (APCs) are introduced as airborne plasmonic hotspots for direct in‐air SERS measurements. APCs function as a macroscale 3D and omnidirectional plasmonic cloud that receives laser irradiation and emits signals in all directions. Importantly, it brings about an effective plasmonic hotspot in a length scale of approximately 2.3 cm, which affords 100‐fold higher tolerance to laser misalignment along the z‐axis compared with 2D SERS substrates. APCs exhibit an extraordinary omnidirectional property and demonstrate consistent SERS performance that is independent of the laser and analyte introductory pathway. Furthermore, the first in‐air SERS detection is demonstrated in stand‐off conditions at a distance of 200 cm, highlighting the applicability of 3D omnidirectional plasmonic clouds for remote airborne sensing in threatening or inaccessible areas.